A matter of sexual confidence: young men's non-prescription use of Viagra in Addis Ababa, Ethiopia. Issue 5 (3rd May 2016) - Both, Rosalijn
Abstract: This paper examines the non-prescription use of the sexual enhancement drug Viagra by young men in Addis Ababa. Data was collected through repeated in-depth interviews with 14 Viagra users – heterosexual men between the ages of 21 and 35 – and focus-group discussions with 21 male and 22 female university students. Study participants turned to Viagra to impress lovers, as a 'support mechanism' when feeling weak or tired, to counteract the effects of chewing the stimulant plant khat and to satisfy what they perceived as a psychological 'addiction'. More generally, young men used Viagra to quell anxieties about what they perceived as women's growing expectations about their sexual performance – informed by changing gender relations and sexual expectations, constructions of masculinity that emphasise sexual prowess, and a misreading of women's sexual desires largely fuelled by the emergence of pornography as a new standard for sexual performance. While some men gained sexual confidence by using Viagra, others – particularly those who used Viagra regularly – paradoxically experienced feelings of loss of manhood.